Proportions of taxa belonging to the gut core microbiome change throughout the life cycle and season of the bark beetle Ips typographus - Veselská, Tereza; Švec, Karel; Kostovčík, Martin; Peral-Aranega, Ezequiel; Garcia-Fraile, Paula; Křížková, Barbora; Havlíček, Václav; Saati-Santamaría, Zaki; Kolařík, Miroslav (FEMS microbiology ecology, 2023)
The European spruce bark beetle, Ips typographus, is a serious pest of spruce forests in Europe, and its invasion and development inside spruce tissues are facilitated by microorganisms. We investigated the core gut bacterial and fungal microbiomes of I. typographus throughout its life cycle in spring and summer generations. We used cultivation techniques and molecular identification in combination with DNA and RNA metabarcoding. Our results revealed that communities differ throughout their life cycle and across generations in proportion of dominantly associated microbes, rather than changes in species composition. The bacteriome consisted mostly of the phylum Gammaproteobacteria, with the most common orders and genera being Enterobacteriales (Erwinia and Serratia), Pseudomonadales (Pseudomonas), and Xanthomonadales. The fungal microbiome was dominated by yeasts (Saccharomycetes-Wickerhamomyces, Kuraishia, and Nakazawaea), followed by Sordariomycetes (Ophiostoma bicolor and Endoconidiophora polonica). We did not observe any structure ensuring long-term persistence of microbiota on any part of the gut epithelium, suggesting that microbial cells are more likely to pass through the beetle's gut with chyme. The most abundant taxa in the beetle's gut were also identified as dominant in intact spruce phloem. Therefore, we propose that these taxa are acquired from the environment rather than specifically vectored between generations.
Keywords: brouci; Picea; kůra rostlin; DNA and RNA metabarcoding; core microbiome; nosatcovití; stadia vývoje; smrk; Gastrointestinal Microbiome; střevní mikroflóra; Plant Bark; Weevils; Animals; roční období; Seasons; zvířata; Coleoptera; Life Cycle Stages; bark beetles; gut fungal and bacterial community; seasonality; Ips typographus